Fixed accuracy confidence interval on the common variance in compound symmetric multivariate normal sampling. Issue 1 (2nd January 2019) - Sarkar, Pritam; Bandyopadhyay, Uttam
Abstract: This work deals with construction of fixed accuracy confidence intervals for the common variance in compound symmetric multivariate normal distribution by adopting a Stein-type two-stage setup and a completely sequential setup. Related asymptotics are developed and the procedures are evaluated by simulation study.